Foreign Gene Expression in the Mouse Cauda Epididymis is Regulated by Androgens (International Journal of Medical and Surgical Sciences, 2015)
This paper deals with the efficiency of in vivo gene transfer to the mouse cauda epididymisand its relation to androgens. Previous experiments in the female reproductive tract have indicated that the efficiency of transfection is related to the hormonal stage of the animal, nevertheless no analysis have been done in the male tract. We used in vivo gene transfer to the mouse cauda epididymis employing a gene construction that expresses the Green Fluorescent Protein (GFP). Untreated and Testosterone treated males were employed. Testosterone injections (5µg/g weight) were done from 2 days before the gene transfer, andtreatment continued each day during a total period of 15 days. Fluorescence microscopy observations showed the expression of GFP in the cytoplasm of the principal cells in the epididymal tubules. The application of the QWin Program that measures the percentage of fluorescent areas showed that they are increased in the epididymis of treated males. This increase was particularly observed two days after gene injections (from 32.24 % in untreated animals to 47.62 % in testosterone treated males) and after seven days (from 29.98 % to 43.05 %). The possibility to improve transfection efficiency would increase the knowledge on epididymal physiology and would permit to modify the fertilizing capacity in mammals.
Keywords: Androgens; Epididymis; Gene transfer; Transfection; Testosterone